Droplet size in a rectangular Venturi scrubber - Costa,M. A. M. (2004)
The Venturi scrubber is a device which uses liquid in the form of droplets to efficiently remove fine particulate matter from gaseous streams. Droplet size is of fundamental importance for the scrubber performance. In the present experimental study, a laser diffraction technique was used in order to measure droplet size in situ in a Venturi scrubber with a rectangular cross section. Droplet size distribution was measured as a function of gas velocity (58.3 to 74.9 m/s), liquid-to-gas ratio (0.07 to 0.27 l/m³), and distance from liquid injection point (64 to 173 mm). It was found that all these variables significantly affect droplet size. The results were compared with the predictions from correlations found in the literature.